2002
DOI: 10.1055/s-2002-19782
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Copper-mediated Intramolecular Amination of Aryl Halides

Abstract: A unique combination of copper iodide and cesium acetate was found to mediate intramolecular amination of aryl halides under mild conditions. The reaction proceeds at room temperature with primary or N-benzyl amines and at moderately elevated temperatures with other amine derivatives. The reaction has been applied to the formation of 5-, 6-, and 7-membered rings. Remarkably, halogens at the meta-position were retained, providing a definitive advantage over palladium-catalyzed systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(58 citation statements)
references
References 2 publications
2
53
0
3
Order By: Relevance
“…[59] In this case, lower temperatures were Fukuyama and co-workers used a novel combination of CuI (2.0 equiv) and CsOAc in an efficient intramolecular cyclization route to dihydroindoles 134 and tetrahydroquinolines 135; reactions were usually complete after 1-24 h at temperatures ranging from room temperature to 90 8C (Scheme 33). [61] This remarkably mild method signifies a breakthrough in the Ullmann condensation reactions at room temperature, although it should be noted that the reaction required 2 equivalents of CuI and that the intermolecular variant failed. The scope of the reaction was established using both o-bromo-and o-iodophenethylamines and a small range of amino-protecting groups (Ac, Ns, Cbz, Bn).…”
Section: The Original Discovery: Catalytic Cu Methods and Substrate Smentioning
confidence: 99%
See 2 more Smart Citations
“…[59] In this case, lower temperatures were Fukuyama and co-workers used a novel combination of CuI (2.0 equiv) and CsOAc in an efficient intramolecular cyclization route to dihydroindoles 134 and tetrahydroquinolines 135; reactions were usually complete after 1-24 h at temperatures ranging from room temperature to 90 8C (Scheme 33). [61] This remarkably mild method signifies a breakthrough in the Ullmann condensation reactions at room temperature, although it should be noted that the reaction required 2 equivalents of CuI and that the intermolecular variant failed. The scope of the reaction was established using both o-bromo-and o-iodophenethylamines and a small range of amino-protecting groups (Ac, Ns, Cbz, Bn).…”
Section: The Original Discovery: Catalytic Cu Methods and Substrate Smentioning
confidence: 99%
“…[73] Strikingly, however, Fukuyama and co-workers have shown that intramolecular C(aryl)ÀN bond formation at room temperature was successful when using 2 equivalents of Cu salt. [61] The key to this mild method relies on the use of CuI and CsOAc, which presumably form CuOAc in situ. The fact that this catalytic system is much less efficient in intermolecular reactions reflects the accelerating effect described by Ma and co-workers on the intermolecular amination of a-and b-amino acids with aryl halides.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many ligands, such as 1,10-phenanthroline [12][13][14][15][16], trans-1,2-cyclohexadiamine [17][18][19][20][21], ethylene glycol [22,23], amino acid [24,25], and other nitrogen, oxygencontaining ligands [26][27][28][29] have been developed under mild condition in copper-catalyzed aminations. However, only several papers have contributed to N-arylation of alkylamines and just a few ligands were found to be effective in these transformation [30][31][32][33]. Furthermore, two major factors that hamper application are the cost and the availability of the catalysts, in particular of the ligand that is often prepared in a tedious multi-step synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although many methods, employing catalytic quantities of either copper (38)(39)(40) or palladium (41), have been described, these are often limited to substrates with little steric occlusion of the amide nitrogen. Use of these conditions with our substrate resulted in little or no observed product.…”
mentioning
confidence: 99%